Reading Literacy of Elementary School Students Based upon PIRLS Framework - Nahdi, Khirjan; Yunitasari, Dukha; Arianti, Baiq Desi Dwi; Atiaturrahmaniah, Atiaturrahmaniah; Usuluddin, Usuluddin (Universitas Hamzanwadi, 2024)
The study focuses on three critical aspects of reading: content comprehension, reading speed, and reading effectiveness. The objective is to understand the literacy competence of these students based on PIRLS parameters and to propose recommendations for enhancing their reading literacy. Data was gathered through reading tests, observations, and interviews. The findings reveal that the student's ability to comprehend reading content falls into the low category, at 0.51%, compared to 15%, 19%, and 24% in IEA countries. Their reading speed is moderate, averaging 151.1 words per minute, within the national average range of 130-180 words per minute. However, according to PIRLS, their reading effectiveness is low, at 34.9%, compared to the 60-80% standard in IEA member countries; the low level of content comprehension, reading effectiveness, and moderate reading speed level can be attributed to external factors. These include the perception of teachers, parents, society, and the government that reading merely involves stringing words together in a broader grammatical context. Internally, students are encouraged to read fluently to gather factual information and to measure the number of words read within a specific timeframe. This study underscores the need for a comprehensive approach to improve reading literacy among fourth-grade students in East Lombok.